Unlocking Novel Functionality: Pseudocapacitive Sensing in MXene-Based Flexible Supercapacitors - Kim, Eunji; Kim, Seongbeen; Jin, Hyeong Min; Kim, Gyungtae; Ha, Hwi‑Heon; Choi, Yunhui; Min, Kyoungha; Cho, Su‑Ho; Han, Hee; Ahn, Chi Won; Roh, Jaewoo; Oh, Il‑Kwon; et al. (Nano-Micro Letters, 2024)
Extensively explored for their distinctive pseudocapacitance characteristics, MXenes, a distinguished group of 2D materials, have led to remarkable achievements, particularly in the realm of energy storage devices. This work presents an innovative Pseudocapacitive Sensor. The key lies in switching the energy storage kinetics from pseudocapacitor to electrical double layer capacitor by employing the change of local pH (-log[H+]) in MXene-based flexible supercapacitors during bending. Pseudocapacitive sensing is observed in acidic electrolyte but absent in neutral electrolyte. Applied shearing during bending causes liquid-crystalline MXene sheets to increase in their degree of anisotropic alignment. With blocking of H+ mobility due to the higher diffusion barrier, local pH increases. The electrochemical energy storage kinetics transits from Faradaic chemical protonation (intercalation) to non-Faradaic physical adsorption. We utilize the phenomenon of capacitance change due to shifting energy storage kinetics for strain sensing purposes. The developed highly sensitive Pseudocapacitive Sensors feature a remarkable gauge factor (GF) of approximately 1200, far surpassing conventional strain sensors (GF: ~ 1 for dielectric-cap sensor). The introduction of the Pseudocapacitive Sensor represents a paradigm shift, expanding the application of pseudocapacitance from being solely confined to energy devices to the realm of multifunctional electronics. This technological leap enriches our understanding of the pseudocapacitance mechanism of MXenes, and will drive innovation in cutting-edge technology areas, including advanced robotics, implantable biomedical devices, and health monitoring systems. Highlights: 1 We have discovered a novel phenomenon where the pseudocapacitance of flexible MXene supercapacitors changes sensitively in response to bending, leading to the development of Pseudocapacitive Sensors. 2 Pseudocapacitive Sensors repurpose supercapacitors as strain sensors, detecting capacitance changes from shifts between pseudocapacitance and electrical double layer capacitor. These highly sensitive sensors have a gauge factor of about 1200, far exceeding that of conventional strain sensors.